Comparative analysis of the association of polymorphism rs9939609 of the FTO gene in patients with type 2 diabetes mellitus in the Tatar and Yakut populations - Farida V. Valeeva; Nadezhda I. Pavlova; Alexey A. Bochurov; Alexey V. Krylov; Lyubov A. Sydykova; Vladislav A. Alekseev; Kamilya B. Khasanova; Ildus I. Ahmetov; Tatyana А. Kiseleva (ZAO "Consilium Medicum", 2024)
Background. One of the most important gene polymorphisms that may be responsible for the development of insulin resistance is the rs9939609 of the FTO gene. Aim. To investigate the association of the rs9939609 polymorphism of the FTO gene in patients with type 2 diabetes (T2D) in the Yakut and Tatar populations. Materials and methods. The study involved patients with T2D from the population of the Yakut nationality of the Republic of Sakha (Yakutia), Yakutsk (n=132) and the Tatar population - residents of the Republic of Tatarstan (n=134). Molecular genetic analysis was carried out on in the central research laboratory of the Department of molecular genetics (Kazan State Medical University) and in the laboratory of hereditary pathology of the Department of Molecular Genetics (Yakut Science Center of Complex Medical Problems). Statistical data processing was carried out using GraphPad InStat, Microsoft Excel 2007 programs. Results. The frequency of the AA genotype of the rs9939609 polymorphism of the FTO gene in the group of T2D in the Tatar population differed from the own control sample: 30.1% vs 14.1%; p=0.00000006, as well as from the European control group from the 1000GENOME database: 30.1% vs 19.9%; p=0.0006. The frequency of the risk allele in T2D group in the Yakut population was statistically significantly higher than in the East Asian control group from the 1000GENOME database (27.7% vs 16.9%; p=0.00007), in the own healthy control group no significant differences were found. Conclusion. The more the Asian component in the genome of the population, the less it is predisposed to obesity and T2D. The rs9939609 polymorphism of the FTO gene is associated with the risk of T2D in the Tatar population; no association in the Yakut population was found.